Verbs and tenses in the Mamluk-Kipchak and Kazakh language (Journal of Oriental Studies, 2022)
This article provides a comparison of typical properties of the principal features of the mainand auxiliary verbs and a study of the tense categories and moods of the historical Mamluk-Kipchaklanguage in comparison with the modern Kazakh language considering such well-known writtensources in the Mamluk-Kipchak language of XIIІ-XV centuries as “Kitab al-Idrak Li-Lisan Al-Atrak”, “Kitab majmua tirjuman turki ua ajami ua muguli ua farsi”, “Kitab ad-durra al-mudiyya fial-luga”, At-turkiya ala at-tamam ua al-kamal” and “Al-Qawanin al-kulliya lidabt al-lugat at-turkiya”. In this regard, descriptions of the mentioned written sources were given first, and a briefoverview of special and general studies on the study of the historical Mamluk-Kipchak language isalso provided.The comparative study showed that the main verbs and auxiliary verbs in the Mamluk-Kipchak language and the modern Kazakh language have structural and semantic similarities, aswell grammatical similarity in terms of tense and mood. The definition of the process of lexical andgrammatical continuity between the historical Mamluk-Kipchak language and the modern Kazakhlanguage, which is the basis of the article, has particular importance from the point of view ofstudying the historical development of the Kazakh language.Key words: Mamluk-Kipchak language, manuscript, Kazakh language, verb, tense category